Puppies, dogs, and blue northers : reflections on being raised by a pack of sled dogs - Paulsen, Gary (Harcourt Brace & Co., 1996)
Minnesota author and dog musher Gary Paulsen reflects on the growth of his sled dogs as he and his animals discover the world around them.